Attempt to Replicate Evidence that Weight and Shape Concerns Amplify the Effects of Gradual Lifestyle Improvement Obesity Prevention Programs. Issue 8 (23rd August 2018) - Stice, Eric; Rohde, Paul
Abstract : See accompanying article, pg.1270 .